Prevalence of hypertension and its associated factors among adults living in Pokhara metropolitan city - Bishnu Gurung; Nirupa Thapa; Usha Kiran Paudel (Journal of Gandaki Medical College, 2022)
Introduction: Hypertension is one of the silent killer diseases affecting multiple organs. Hypertension prevalence is increasing in developing countries. So, the present study was conducted to find out the prevalence and associated factors of hypertension among adults living in Pokhara metropolitan city.